2020
DOI: 10.1111/and.13697
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose heavy metal mixture (lead, cadmium and mercury)‐induced testicular injury and protective effect of zinc andCostus aferin wistar albino rats

Abstract: Global concern about male infertility is growing, and this affects approximately 50% of infertile couples (Agarwal, Mulgund, Hamada, & Chyatte, 2015). Environmental and occupational exposures to heavy metals have led to various deleterious damages to the biological system, of which infertility is one. The results of various studies associate male factors with infertility in 20%-50% of cases (Boivin, Bunting, Collins, & Nygren, 2007; Jarow et al., 2002). Aetiological factors implicated in male infertility can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…The antioxidant indicators (catalase, CAT; superoxide dismutase, SOD; and GSH) were reduced, and the lipid peroxidation marker was raised by a low-dose heavy metal combination (LDHMM; PbCl 2 +CdCl 2 +HgCl 2 ). Costus afer treatment decreased LDHMM-mediated toxicity in rats in a dose-dependent manner [49]. The results of this study indicate that treatment with HgCl 2 (5 mg/kg bw) on d-1 signi cantly increased MDA levels compared to the control on d-7.…”
Section: Discussionmentioning
confidence: 53%
“…The antioxidant indicators (catalase, CAT; superoxide dismutase, SOD; and GSH) were reduced, and the lipid peroxidation marker was raised by a low-dose heavy metal combination (LDHMM; PbCl 2 +CdCl 2 +HgCl 2 ). Costus afer treatment decreased LDHMM-mediated toxicity in rats in a dose-dependent manner [49]. The results of this study indicate that treatment with HgCl 2 (5 mg/kg bw) on d-1 signi cantly increased MDA levels compared to the control on d-7.…”
Section: Discussionmentioning
confidence: 53%
“…30 In various studies, it was reported that radical production increases as a result of mercury chloride exposure, leading to lipid peroxidation in the cell and causing damage in many tissues, especially in the kidney and liver. 2,30,31 In this study, it was found that liver and kidney MDA levels were significantly increased as a result of mercury chloride exposure (Tables 1 and 2). The increase in liver and kidney MDA levels is a clear indication that mercury chloride exposure causes oxidative damage.…”
Section: Discussionmentioning
confidence: 53%
“…Although MDA is the end product formed after the peroxidation of unsaturated fatty acids, it is an important lipid peroxidation marker to show the level of damage indirectly, although not directly 30 . In various studies, it was reported that radical production increases as a result of mercury chloride exposure, leading to lipid peroxidation in the cell and causing damage in many tissues, especially in the kidney and liver 2,30,31 . In this study, it was found that liver and kidney MDA levels were significantly increased as a result of mercury chloride exposure (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 55%